Reflexiones sobre la reforma del recurso de casación civil - Hinojosa Segovia, Rafael (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2024)
By this piece of work, the author carries out a study on the reform of the civil cassation appeal carried out, mainly, by Royal Decree- Law 5/2023, dated 28 June, by which with the new regulation, which came into force on July 29, 2023, it is intended to unload matters from the First Chamber of the Supreme Court, given the saturation situation it is experiencing, so that the response to the resources raised is within a reasonable period of time. Thus, the new configuration of the aforementioned appeal is analyzed, eliminating the split into an extraordinary appeal for procedural infringement and appeal for cassation, established by the Law 2000 on Civil Procedure and now opting only for a single extraordinary appeal, that of cassation, to through which both violations of procedural law and material law must be articulated. Likewise, it stops at the analysis of the cassation interest as a preferential and almost exclusive means of the aforementioned appeal, examining the procedure, with special emphasis on the admission phase. Likewise, it refers to Royal Decree-Law 6/2023, of December 19, by which certain modifications are carried out and some omissions are corrected in the regulation of the aforementioned resource, whose entry into force is March 20, 2024. Furthermore, the new regulations continue to favor the primacy of the ius constitutionis, in terms of the defense of the law and jurisprudential unification, to the detriment of the ius litigatoris, which should not be forgotten, because ultimately Justice is at the service of the citizen to resolve its claims.